PENGARUH KUALITAS PELAYANAN DAN PROMOSI PENJUALAN TERHADAP MINAT BELI PADA KONSUMEN INDOMARET DI WILAYAH SURABAYA - Nico Rudi Hermansah (Jurnal Performa)
The backgound of this research is the change of consumer behavior in shopping, today's society is more confident about ordering products that they really need at retail that already has a brand. . The national retail industry which is experiencing growth motivates local retailers for the retail industry in the regions to experience development. Minimarkets also participate in revitalizing the retail industry in Indonesia by creating trading centers near settlements. So far, many retailers have been seen competing to open retail stores. Indomaret is a franchise distribution chain actually controlled by PT Indomarco Prismatama (parent company PT Indoritel Makmur Internasional Tbk), which is a subsidiary of the Salim Group. Indomaret provides a variety of basic and daily needs for the community, which until now has 18,271 stores, most of Indonesia. This study uses sales promotion and service quality which represent independent variables that affect the dependent variable, namely buying interest of Indomaret consumers in Surabaya with data collection techniques through questionnaires. This research was conducted on a population of people who had shopped at Indomaret in the city of Surabaya with a total sample of 100 respondents. This study uses multiple linear regression analysis method with data processing using SPSS 25, the results of data processing indicate that sales promotion and service quality have a positive and significant effect on consumer purchase intention.